Projeto e construção de lajes nervuradas de concreto armado - Silva, Marcos Alberto Ferreira da (2005)
The demand for simple and efficient solutions is increasing in civil construction, wherein the reduction of costs and the increase of speed and versatility within the applications are required. Due to its advantages, reinforced concrete ribbed slabs have been consolidated as an excellent alternative to compose buildings floors. The present research deals with this type of slab, disseminating its constructive characteristics, variations, structural behavior and the main recommendations proposed by different authors and addressing to all potential users (designers, constructors, contractors); recommendations, calculation methods to determine the internal forces and displacements, design and construction procedures according to the Brazilian code of practice NBR 6118:2003 are presented. Additionally, illustrative examples with the calculation, the detailing and the verifications of the serviceability limit state (crack width and extreme deformation) are presented. Finally, the results obtained from the examples simulating ribbed slabs in two directions are compared with the results obtained from the consideration of a massive slab.